Sound for digital video - Holman, Tomlinson (Focal Press, 2013)
"Achieve professional quality sound on a limited budget! Harness all new, Hollywood style audio techniques to bring your independent film and video productions to the next level. In Sound for Digital Video, Second Edition industry experts Tomlinson Holman and Arthur Baum give you the tools and knowledge to apply recent advances in audio capture, video recording, editing workflow, and mixing to your own film or video with stunning results. This fresh edition is chockfull of techniques, tricks, and workflow secrets that you can apply to your own projects from preproduction through postproduction. New to this edition:A new feature on "true" 24p shooting and editing systems, as well as single vs. double-system recordingA strong focus on new media, including mini-DVDs, hard disks, memory cards, and standard and high-definition imagery Discussion of camera selection, manual level control, camera and recorder inputs, location scouting, and preproduction planningInstruction in connectors, real-time transfers, and file-based transfers from DVDs, hard drives, and solid state media. Blu-Ray and HD tape formats for mastering and distribution in addition to file-based, DV, and DVD masters. A revamped companion website, www.focalpress.com/cw/holman, featuring recording and editing exercises, examples and sample tracks Whether you are an amateur filmmaker who wants to create great sound or an advanced professional in need of a reference guide, Sound for Digital Video, Second Edition is an essential addition to your digital audio tool belt."--Provided by publisher